Partner notification for HIV and syphilis: effects on sexual behaviors and relationship stability. - Kissinger, Patricia J; Niccolai, Linda M; Magnus, Manya; Farley, Thomas A; Maher, Julie E; Richardson-Alston, Gwangi; Dorst, Dennis; Myers, Leann; Peterman, Thomas A (Sexually transmitted diseases, 2003)
Partner notification (PN), originally designed for syphilis control, has been used to control the spread of HIV since 1985. Because HIV infection is noncurable, the benefit of contact tracing and treatment demonstrated for the control of syphilis may not apply to HIV. For HIV, PN must facilitate behavior change that will reduce the spread of the infection. One concern is that HIV PN can promote the breakup of old partnerships and increase the acquisition of new partners, thereby spreading HIV infections.
Keywords: Adolescent; Adult; Cohort Studies; Contact Tracing; Female; HIV Infections; Humans; Interpersonal Relations; Louisiana; Male; Prospective Studies; Sexual Behavior; Sexual Partners; Spouse Abuse; Syphilis